2017
DOI: 10.31227/osf.io/vr8z4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of Simple Additive Weighting Algorithm in Particular Instance

Abstract: In the problem of determining the proper level of sequence in a sorting problem, the Simple Additive Weighting (SAW) method is an easy-to-use technique. It can analyze cases based on the criteria used. The use of criteria values in this approach has an unlimited amount. The more criteria used, the higher the accuracy of the results obtained. There are two types of criteria, cost, and benefits. Cost is used if the higher the criterion value, the lower the chance to get the top score while the benefit is used if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
1
5
0
3
Order By: Relevance
“…The results of this research are fitted to the Liu, Xu, Fu, Li, and Faiz (2019) results in terms of capability of multicriteria decision‐making (MCDM) models in omitting redundant indicators and introducing effective indicators in each decision‐making problem. Other obtained results tend to be similar to results of Karlitasari et al (2017), Siahaan et al (2017), Srdjevich and Medeiros (2008) and Turskis (2008), which indicated that SAW model includes high level of accuracy and low level of complexity as well as it is a reliable model.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this research are fitted to the Liu, Xu, Fu, Li, and Faiz (2019) results in terms of capability of multicriteria decision‐making (MCDM) models in omitting redundant indicators and introducing effective indicators in each decision‐making problem. Other obtained results tend to be similar to results of Karlitasari et al (2017), Siahaan et al (2017), Srdjevich and Medeiros (2008) and Turskis (2008), which indicated that SAW model includes high level of accuracy and low level of complexity as well as it is a reliable model.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
“…The only calculation that is done by this method is to produce the biggest value, which is later used as the best alternative. This method is more efficient than other methods because the time required for computation is shorter (Siahaan, Elviwani, Surbakti, & Lubis, 2017). Also, the SAW method does not depend on the data pattern (Karlitasari, Suhartini, & Benny, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Metode Simple Additive Weighting merupakan metode yang dapat melakukan perangkingan dengan penjumlahan terbobot pada setiap nilai alternatif [6], [18], [19].…”
Section: Simple Additive Weightingunclassified
“…Metode Simple Additive Weighting merupakan metode yang dapat melakukan perangkingan dengan penjumlahan terbobot pada setiap nilai alternatif [16]- [18]…”
Section: Simple Additive Weighting(saw)unclassified